Superior mesenteric artery syndrome - Bernotavičius, Giedrius; Saniukas, Kęstutis; Karmonaitė, Irena; Zagorskis, Rimantas (Acta medica Lituanica, 2016)
Background. An obstruction of the distal part of the duodenum can occur because of the superior mesenteric artery syndrome (SMAS) after a surgical correction of scoliosis. It is essential to evaluate the risk factors and diagnose the SMAS in time because complications of this condition are life-threatening and it is associated with a high rate of morbidity. Diagnostics of the SMAS is challenging, because it is rare and its symptoms are non-specific. Therefore, in order to better understand the essence of this pathology and to make diagnosis easier we present a rare clinical case of the superior mesenteric artery syndrome after a surgical correction of neuromuscular scoliosis. The clinical case. A 12-year-old girl with a specific development disorder, sensory neuropathy and progressive kypho-scoliosis was admitted to Vilnius University Children’s Hospital. The patient had right side 50-degree thoracic scoliosis and an 80-degree thoracic kyphosis. She underwent posterior spinal fusion with hooks and screws from Th1 to L2. On the fourth day after the surgery the patient developed nausea and began to vomit each day 1-2 times per day, especially after meals. The SMAS was suspected and a nasogastric tube was inserted, stomach decompression and the correction of electrolytes disbalance were made. After the treatment, the symptoms did not recur and a satisfactory correction and balance of the spine were made in coronal and sagittal planes. Conclusions. It is extremely important to identify the risk factors of the SMAS and begin preoperative diet supplements before surgical correction of scoliosis for patients with a low body mass index. After the first episode of vomiting following the surgery, we recommend to investigate these patients for a gastrointestinal obstruction as soon as possible. Decompression of the stomach, enteral or parenteral nutrition, and fluid therapy are essential in treating the SMAS.